The magic of computer graphics : landmarks in rendering - Kurachi, Noriko (A K Peters, 2011)
Computer graphics is a vast field that is becoming larger every day. It is impossible to cover every topic of interest, even within a specialization such as CG rendering. For many years, Noriko Kurachi has reported on the latest developments for Japanese readers in her monthly column for CG World. Being something of a pioneer herself, she selected topics that represented original and promising new directions for research. Many of these novel ideas are the topics covered in The Magic of Computer Graphics. Starting from the basic behavior of light, the first s.